Phonological constituents and their movement in Latin*. Issue 1 (15th June 2016) - Agbayani, Brian; Golston, Chris
Abstract : We document a fronting process in Latin that is difficult to model as syntactic movement but fairly easy to model as phonological movement. Movement with similar properties has been observed elsewhere in Classical Greek, Russian, Irish and Japanese; we suggest that the Latin movement is of the same type and takes place in the phonological component of the grammar, following the mapping from syntactic to prosodic structure.